The Effectiveness of Chlorine Tablets to Reducing Coliform in Wastewater Treatment Plant - Sri Arofah Mulyati; Mia Azizah; Srikandi Srikandi; Maidaswar Maidaswar; Neneng Atikah (JURNAL SAINS NATURAL, 2022)
Wastewater originating from experimental animal cages that are not treated properly can be a source of pollution because it contains organic, inorganic materials and even pathogenic microorganisms. Disinfection using chlorine is the last step in the wastewater treatment process to reduce microorganisms. This study aimed to determine the effectiveness of chlorine tablets in reducing the content of Coliform from experimental animal cage wastewater at the Wastewater Treatment Plant (WWTP) to meet the Total Coliform quality standard in the Regulation of the Minister of Environment and Forestry No. 68 of 2016 concerning domestic wastewater quality standards. The research was conducted using laboratory experiments pre and post-test. Wastewater samples were taken from 2 points, namely, the point inlet (before treatment) and outlet (after chlorination), the MPN test Coliform (SNI 2897 2008) were repeated twice, and the measured pH and temperature to analyze environmental factors. The results showed that 200 g of chlorine tablets could effectively reduce Coliform up to 98.55% and meet the quality standards used as a reference.Keywords: Coliform, Chlorine, Wastewater, WWTP, Quality standard Efektivitas Tablet Klorin Dalam Menurunkan Kandungan Coliform Pada Instalasi Pengolahan Air LimbahABSTRAKAir limbah yang berasumber dari kandang hewan coba yang tidak diolah dengan tepat dapat menjadi sumber pencemaran karena mengandung bahan organik, anorganik bahkan mikroorganisme pathogen. Desinfeksi meggunakan klorin merupakan tahapan terakhir pada proses pengolahan air limbah untuk mengurangi mikroorganisme. Tujuan dari penelitian ini adalah mengetahui efektivitas tablet klorin dalam menurunkan kandungan Coliform dari air limbah kandang hewan coba di Instalasi Pengolahan Air Limbah (IPAL) agar memenuhi baku mutu Total Coliform dalam Peraturan Menteri Lingkungan Hidup dan Kehutanan No. 68 Tahun 2016 tentang baku mutu air limbah domestik. Penelitian dilakukan dengan menggunakan eksperimen laoboratorium pre dan post test. Sampel air limbah diambil dari 2 titik yaitu titik inlet (sebelum pengolahan) dan outlet (sesudah klorinasi), uji MPN Coliform (SNI 2897 2008)  dilakukan dua kali ulangan, serta mengukur pH dan suhu untuk menganalisis faktor lingkungan. Hasil penelitian menunjukkan tablet klorin sebanyak 200 g efektif dapat menurunkan Coliform hingga 98,55 % dan memenuhi baku mutu yang dijadikan acuan.Kata Kunci: Coliform, Klorin, air limbah, IPAL dan baku mutu.